Classification of 3-dimensional complex diassociative algebras - Rikhsiboev, Ikrom M.; Rakhimov, samiddin Sattarovich; Basri, Witriany (Institute for Mathematical Research, Universiti Putra Malaysia, 2010)
The paper deals with the classification problems of a subclass of finite-dimensional algebras. One considers a class of algebras having two algebraic operations with five identities. They have been called diassociative algebras by Loday. In this paper we describe all diassociative algebra structure in complex vector space of dimension at most three.